Some Candidate Drugs for Pharmacotherapy of Alzheimer's Disease - Barbara Miziak; Barbara Błaszczyk; Stanisław J. Czuczwar (MDPI AG, 2021)
Alzheimer's disease (AD; progressive neurodegenerative disorder) is associated with cognitive and functional impairment with accompanying neuropsychiatric symptoms. The available pharmacological treatment is of a symptomatic nature and, as such, it does not modify the cause of AD. The currently used drugs to enhance cognition include an N-methyl-d-aspartate receptor antagonist (memantine) and cholinesterase inhibitors. The PUBMED, Medical Subject Heading and Clinical Trials databases were used for searching relevant data. Novel treatments are focused on already approved drugs for other conditions and also searching for innovative drugs encompassing investigational compounds. Among the approved drugs, we investigated, are intranasal insulin (and other antidiabetic drugs: liraglitude, pioglitazone and metformin), bexarotene (an anti-cancer drug and a retinoid X receptor agonist) or antidepressant drugs (citalopram, escitalopram, sertraline, mirtazapine). The latter, especially when combined with antipsychotics (for instance quetiapine or risperidone), were shown to reduce neuropsychiatric symptoms in AD patients. The former enhanced cognition. Procognitive effects may be also expected with dietary antioxidative and anti-inflammatory supplements-curcumin, myricetin, and resveratrol. Considering a close relationship between brain ischemia and AD, they may also reduce post-brain ischemia neurodegeneration. An investigational compound, CN-105 (a lipoprotein E agonist), has a very good profile in AD preclinical studies, and its clinical trial for postoperative dementia is starting soon.